Citizenship after the Nation State : regionalism, nationalism and public attitudes in Europe - Henderson, Ailsa; Jeffery, Charlie; Wincott, Daniel; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Offering an confrontation of the uncritical choice of the'nation-state' as a unit of analysis in postwar social science, this book utilises specially collected data from 14 regions across five European states to explores how citizens define and pursue collective goals at regional scale as well as at the scale of the'nation-state'.
Keywords: Science; Science; Science, general